2016
DOI: 10.3389/fmicb.2015.01526
|View full text |Cite
|
Sign up to set email alerts
|

An Intracellular Arrangement of Histoplasma capsulatum Yeast-Aggregates Generates Nuclear Damage to the Cultured Murine Alveolar Macrophages

Abstract: Histoplasma capsulatum is responsible for a human systemic mycosis that primarily affects lung tissue. Macrophages are the major effector cells in humans that respond to the fungus, and the development of respiratory disease depends on the ability of Histoplasma yeast cells to survive and replicate within alveolar macrophages. Therefore, the interaction between macrophages and H. capsulatum is a decisive step in the yeast dissemination into host tissues. Although the role played by components of cell-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Fungal biofilms are sessile communities of microorganisms, which cells adhere to each other and to biotic or abiotic substrate, usually surrounded by an extracellular matrix of polysaccharides ( Costa-Orlandi et al, 2017 ). Biofilm cells have structural, functional, and genetic differences in relation to planktonic cells ( Kuhn and Ghannoum, 2004 ; Mowat et al, 2007 ; Ramage et al, 2009 ; Pitangui et al, 2012 , 2016 ). The biofilm morphology can be influenced by the quality and quantity of available nutrients, such as the composition of the culture medium ( Kucharíkova et al, 2011 ; Lee et al, 2013 ; Serrano-Fujarte et al, 2015 ) and the oxygen concentration ( Stichternoth and Ernst, 2009 ; Bonhomme et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fungal biofilms are sessile communities of microorganisms, which cells adhere to each other and to biotic or abiotic substrate, usually surrounded by an extracellular matrix of polysaccharides ( Costa-Orlandi et al, 2017 ). Biofilm cells have structural, functional, and genetic differences in relation to planktonic cells ( Kuhn and Ghannoum, 2004 ; Mowat et al, 2007 ; Ramage et al, 2009 ; Pitangui et al, 2012 , 2016 ). The biofilm morphology can be influenced by the quality and quantity of available nutrients, such as the composition of the culture medium ( Kucharíkova et al, 2011 ; Lee et al, 2013 ; Serrano-Fujarte et al, 2015 ) and the oxygen concentration ( Stichternoth and Ernst, 2009 ; Bonhomme et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have reported that cultured alveolar macrophages are apoptotic within 24 h after incubation with Histoplasma at a multiplicity of five yeasts per cell, and this is suggested to be due to the expression of calcium binding protein (CBP), a yeast-specific secreted effector (38,39). Pitangui et al examined the interaction of Histoplasma with AMJ2-C11 alveolar macrophages and found that apoptosis occurs within 5 h after incubation with a 5:1 ratio of yeasts to cells (40). In that study, the authors noted that microscopic imaging revealed that individual cells contain up to 24 to 30 yeasts, and thus, it is not surprising that apoptosis occurs rapidly in that scenario (40).…”
Section: Discussionmentioning
confidence: 99%
“…Pitangui et al examined the interaction of Histoplasma with AMJ2-C11 alveolar macrophages and found that apoptosis occurs within 5 h after incubation with a 5:1 ratio of yeasts to cells ( 40 ). In that study, the authors noted that microscopic imaging revealed that individual cells contain up to 24 to 30 yeasts, and thus, it is not surprising that apoptosis occurs rapidly in that scenario ( 40 ). Indeed, the multiplicity of infection has been directly correlated with cell death after in vitro infection ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Growth in a mass increases the resistance of the organisms to environmental stress, their resistance to antifungal activities and also effectively shields them from attack by phagocytes (Williams and Ramage, 2015). Fungi that are capable of forming biofilms are C. albicans (Zelante et al, 2012), C. neoformans, H. casulatum, P. brasiliensis , and A. fumigatus (Ramage et al, 2009; Pitangui et al, 2015; Sardi et al, 2015). …”
Section: Stealthmentioning
confidence: 99%